Phosphorus Changes In Intensive Cropping Paddy Soil Under Natural And Controlled Conditions From Mada, Kedah - Yusoff, Muhammad Izzuddin (2019)
Phosphorus is one of the primary nutrients needed by plant to perform its activities. However, phosphorus in soil can easily being fixed. In agricultural soil, phosphorus was mainly supplied by fertilizer application. Majority of farmers tend to apply more phosphorus fertilizer to increase yield and this practice may lead to nutrient concentration changes in soil particularly phosphorus pools. Therefore, this study was carried out to determine the changes of phosphorus pool in paddy soil from MADA, Kedah which was known to practice intensive paddy cropping for almost 50 years. In order to determine phosphorus status and changes in paddy soil, experiments was conducted under two environmental conditions; natural (field sampling) and controlled (plant house study). In controlled condition, three treatments such as inorganic fertilizer, vermicast and control were applied to study the changes of phosphorus concentration in two cropping periods. Soil parameters measured were soil texture, soil pH and soil nutrients (organic matter, nitrogen and phosphorus) while the plant parameters measured were biomass and plant nutrients. To determine the phosphorus pool in soil, sequential phosphorus fractionation was carried out. Under natural condition, the changes in phosphorus pool in different soils were varied significantly due to different soil pH and soil texture.